Peranan Tokoh Agama Islam Dan Hindu Dalam Menjaga Kerukunan Umat Beragama Di Kota Bandar Lampung - Ulfah, Khoiriya; Wulandari, Deshinta Nurul (Universitas Islam Negeri Raden Intan Lampung, 2021)
Religious leaders play an important role in maintaining community harmony in Labuhan Dalam Village. Because, basically Islamic religious leaders and Hindu religious leaders are used as examples or role models in everyday life for the Muslim community and Hindus in Labuhan Dalam Village. In everyday life, Islamic religious leaders and Hindu religious leaders have a large enough contribution to the harmony of religious communities around them. The influence comes from the leadership spirit that is attached to the person of the religious figure. In addition to having responsibilities in every religious activity, the role of religious leaders also invites and directs the community to do positive things, improve religious rituals according to the teachings of each religion, monitor the religious conditions of the community, hold religious activities, hold community leaders meetings. , open inter-religious mediation in the event of a dispute. This research is included in the field research (field research) with the type of qualitative research that is descriptive. The research location is located in Labuhan Dalam Village. This study uses qualitative research methods using a Sociological approach. The data collection procedures to support the research were carried out by observation, interviews, and documentation. In this study, there are two sources of data used by the author, namely primary data and secondary data. The role of a religious figure is very large in influencing social life. The designation of religious figures in Islam is ustadz, kyai or ulama while Hindu religious figures are called Stakeholders. These two figures are very influential in maintaining harmony for the community in Labuhan Dalam Village. This is proven as what the researchers found that, in their daily life, the people of Labuhan Dalam maintain mutual tolerance between religious communities. This is because each religious leader always teaches his people to help each other without discriminating, teaches an attitude of openness, gives deep understanding in maintaining communication between others. It is proven by the fact that on religious holidays in each religion, Muslims and Hindus help each other to maintain conditions that are not conducive. So, that is the success factor of religious leaders in maintaining harmony in Labuhan Dalam Village. The obstacle to the realization of religious harmony in Labuhan Dalam Village is due to some individuals who are too fanatical about their religion and are too closed off, resulting in a lack of discussion space between the surrounding community. However, this can be overcome through regular deliberations held by religious leaders, so as to prevent conflicts between religious communities.